Donor substrate flexibility study of AtUGT89C1, a glycosyltransferase from Arabidopsis thaliana. Issue 7 (1st September 2016) - Parajuli, Prakash; Pandey, Ramesh Prasad; Darsandhari, Sumangala; Park, Yong Il; Sohng, Jae Kyung
GRAPHICAL ABSTRACT: ABSTRACT: AtUGT89C1, a glycosyltransferase from Arabidopsis thaliana, has shown interesting characteristics such as accepting diverse NDP-D/L-sugars as glycosyl donors. Genistein was used as a substrate to probe in vitro reactions in which different NDP-sugars were used as sugar donors. Among nine different NDP-D/L-sugars tested, AtUGT89C1 accepted five of them, including UDP-α-D-glu-cose, UDP-α-D-galactose, dTDP-β-L-rhamnose, GDP-β-L-fucose, and dTDP-α-2-deoxy-D-glucose and conjugated sugar moieties from the respective donors with the 7-hydroxyl position of genistein. Results showed the promiscuous nature of AtUGT89C1 toward donor and acceptor substrates, thus expanding the biotechnological application of this enzyme in the production of natural and unnatural flavonoid glycosides.